2010
DOI: 10.1177/230949901001800124
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Cement-Loaded Kuntscher Nail in First-Stage Revision Hip Arthroplasty for Massive Femoral Bone Loss Secondary to Infection: A Report of Four Cases

Abstract: A 2-stage revision total hip replacement (THR) is the standard treatment for a chronically infected THR with severe metadiaphyseal bone loss. A long-stem cemented prosthesis as part of a temporary articular spacer is commonly used during the first-stage procedure. Nonetheless, this option is expensive and can pose difficulties for patients with a small medullary canal. A construct using an antibiotic cement-loaded Kuntscher nail cemented with a highly polished Exeter stem has been devised and used in 4 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The use of articulating spacers for massive femoral bone defects has been described before [3] ( Table 2 ). However, the use of Rush or Kirschner pins is associated to a high pin fracture rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of articulating spacers for massive femoral bone defects has been described before [3] ( Table 2 ). However, the use of Rush or Kirschner pins is associated to a high pin fracture rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are number of alternatives for preparing these articulating spacers, eg, manually, using silicon/metal molds, commercial spacers, or directly implanting a cemented prosthesis on a temporary basis, very little information is available on the use of such spacers in massive bone defects or defects affecting the entire femur [3] . To our knowledge, there are only 2 reports in the literature on the preparation of femur spacers using a cemented intramedullary nail with a hip stem [3] or PROSTALAC type spacer [4] . In both publications, the knee joint was “sacrificed,” affixing the distal zone of the nail in the proximal tibia.…”
Section: Introductionmentioning
confidence: 99%
“…A cement spacer loaded with antibiotics is used, this is either pre-manufactured or constructed at the time of surgery [160,161]. Various techniques described in the construction of a cement loaded spacer, the technique used depends on the joint involved and the level of bone loss encountered during the first stage [109,[161][162][163][164]. These custom spacers allow antibiotic elution locally to eradicate the infective organism and maintain soft tissue balance to accommodate the definitive implant during the second stage.…”
Section: Two Stage Revision Arthroplastymentioning
confidence: 99%
“…Richards et al 33 reported good success with a novel technique that uses an antibiotic cement-loaded Küntscher nail cemented with a highly polished femoral stem as a temporary spacer in the setting of massive femoral bone loss. Richards et al 33 reported good success with a novel technique that uses an antibiotic cement-loaded Küntscher nail cemented with a highly polished femoral stem as a temporary spacer in the setting of massive femoral bone loss.…”
Section: Special Considerations For Challenging Casesmentioning
confidence: 99%